After the bell : family background, public policy, and educational success - Conley, Dalton, 1969-; Albright, Karen, 1973- (Routledge advances in sociology, 2004)
This book looks at the social and economic factors of schooling and will prove an intriguing read for sociologists, social economists and policy-makers alike.